Geology of North Africa - Tawadros, E. (CRC Press, 2012)
"An expanded and updated edition of the original 'Geology of Egypt and Libya'. New chapters covering the geology of Algeria, Tunisia and Morocco have been added to cover all of North Africa. Moreover, the petroleum systems of North Africa are now also discussed and new chapters on the history of geological exploration in Egypt and Libya have been added. This reference volume deals reviews the tectonic elements, the geology of the Pan-African Shield, and Phanerozoic geological evolution of the five North African countries, and describes most of the lithostratigraphic units. Including over 2500 literature references, this volume is an essential information source for.
Rev. ed. of: Geology of Egypt and Libya / E. Tawadros. 2001.
"A Balkema book."
Keywords: Geology -- Egypt.; Geology -- Libya.; Geology -- Africa, North.; elektronické knihy; electronic books